Intervention in cases of female victims of domestic violence - Deza Villanueva, Sabina (2001)
The attention to domestic violence victims is madre in most of the cases in the context of a crisis intervention. We have to note that there is a great personal, physical and psychological cost in a crisis and if it is not adequalety it can lead to a long term psychic damage. Intervention choices are explained.